Of cows and men: Nationalism and Australian cow making - Fozdar, Farida (The Australian journal of anthropology, 2014)
This article explores why cows were identified as Australian in a public debate over the treatment of cattle in Indonesian abattoirs. Using a discursive approach applied to data extracted from media coverage, the article traces the debate, beginning with the ways Australian-ness was constructed before moving on to consider the implications of this construction in relation to nationalism and rights. The article argues that making the cows Australian had two functions. By being treated as autochthonous they were presumed to hold a certain set of rights which justified interference in practices occurring in an independent sovereign nation. Second, the nationalism implicit in the rendering of animals as Australian functioned to contrast Australia's ‘civilisation’ with Indonesian (and Islam's) ‘barbarism’, allowing Australia to re-assert a sense of itself as humanitarian. This was particularly relevant in a context where that humanity was in question due to Australia's treatment of asylum seekers.